2007
DOI: 10.1175/2007waf2006017.1
|View full text |Cite
|
Sign up to set email alerts
|

A Fuzzy Logic–Based Analog Forecasting System for Ceiling and Visibility

Abstract: WIND-3 is an application for aviation weather forecasting that uses the analog method to produce deterministic predictions of cloud ceiling height and horizontal visibility at airports. For data, it uses historical and current airport observations [routine aviation weather reports (METARs)], and model-based guidance. It uses the perfect prognosis assumption as it is designed to use any model-based predictions of wind direction and speed, temperature and humidity, and precipitation occurrence and type to specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…Mueller et al (2003) and showed that fuzzy logic can be used for nowcasting in various ways. In addition, Hansen (2007) and Leyton and Fritsch (2003) used fuzzy logic for forecasting ceiling and visibility. TMF for lightning forecasting can be derived from a combination of normalized membership functions of the selected parameters with proper weights.…”
Section: Tmf From Fuzzy Logic Algorithmmentioning
confidence: 99%
“…Mueller et al (2003) and showed that fuzzy logic can be used for nowcasting in various ways. In addition, Hansen (2007) and Leyton and Fritsch (2003) used fuzzy logic for forecasting ceiling and visibility. TMF for lightning forecasting can be derived from a combination of normalized membership functions of the selected parameters with proper weights.…”
Section: Tmf From Fuzzy Logic Algorithmmentioning
confidence: 99%
“…(Bankert and Hadjimichael 2007;Hansen 2007;Martin 1972;Vislocky and Fritsch 1997, hereafter VF97;Wiener et al 2004). These techniques are usually applied in very short-range forecasting from 0 up to approximately 6 h in the future.…”
Section: A Obs-based Sky Condition Forecastingmentioning
confidence: 99%
“…More advanced nonparametric, predictive learning algorithms, trained on past surface observations, have been applied to cloud forecasting by several investigators. Hansen (2007) used a statistical, analog forecasting method based on a k-nn algorithm similar to the present investigation to predict cloud ceiling height and surface visibility. Bankert and Hadjimichael (2007) applied a similar RP technique to archived model fields to predict cloud ceiling height.…”
Section: A Obs-based Sky Condition Forecastingmentioning
confidence: 99%
See 1 more Smart Citation
“…Hansen has used fuzzy K-NN weather forecasting system to improve the technique of persistence climatology by using past and present cases [22]. A neural-fuzzy system for modeling wet season tropical rainfall has been used [23].…”
Section: Introductionmentioning
confidence: 99%